Effect of water temperature on biofouling development in reverse osmosis membrane systems. (15th October 2016) - Farhat, N.M.; Vrouwenvelder, J.S.; Van Loosdrecht, M.C.M.; Bucs, Sz.S.; Staal, M.
Abstract: Understanding the factors that determine the spatial and temporal biofilm development is a key to formulate effective control strategies in reverse osmosis membrane systems for desalination and wastewater reuse. In this study, biofilm development was investigated at different water temperatures (10, 20, and 30 °C) inside a membrane fouling simulator (MFS) flow cell. The MFS studies were done at the same crossflow velocity with the same type of membrane and spacer materials, and the same feed water type and nutrient concentration, differing only in water temperature. Spatially resolved biofilm parameters such as oxygen decrease rate, biovolume, biofilm spatial distribution, thickness and composition were measured using in-situ imaging techniques. Pressure drop (PD) increase in time was used as a benchmark as to when to stop the experiments. Biofilm measurements were performed daily, and experiments were stopped once the average PD increased to 40 mbar/cm. The results of the biofouling study showed that with increasing feed water temperature (i) the biofilm activity developed faster, (ii) the pressure drop increased faster, while (iii) the biofilm thickness decreased. At an average pressure drop increase of 40 mbar/cm over the MFS for the different feed water temperatures, different biofilm activities, structures, and quantities were found, indicating that diagnosis of biofouling of membranes operated at different or varying (seasonal) feed water temperatures may be challenging. Membrane installations with a high temperature feed water are more susceptible to biofouling than installations fed with low temperature feed water. Graphical abstract: Highlights: Impact of temperature on biofilm development in RO systems has been evaluated. Biofilm growth and pressure drop increase were faster at higher water temperature. Biofilm thickness decreased at higher feed water temperatures. Biomass accumulation decreased at higher feed water temperatures. Biofilm structure and composition highly affected the pressure drop increase.